Rancang Bangun Sistem Informasi Kas pada Ikatan Remaja Pesantren Akmaliah Berbasis Web - Akbar, Yuma; Azis, Iim Muhaemin Abdul; Farhani, Aulia; Nufus, Reda Hayati (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Ikatan Remaja Pondok Pesantren Akmaliah (IKRA) is a management organization within the Akmaliah Islamic Boarding School. Akmaliah Islamic Boarding School is a place for teaching or studying Islamic teachings. Based on information from one of the administrators of the IKRA organization, there are problems with the management system and cash contributions at this organization called IKRA. In the previous cash system, recording of outgoing and incoming funds was still done manually and information about the recording was still done manually, namely through the WhatsApp Group social media application. This research aims to develop a Web-based cash information system for the Akmaliah Islamic Boarding School Youth Association Organization. The development of this system was carried out using the PHP programming language with the database management used being MySQL. The results of developing this system produce a cash management website that can be managed by every IKRA member online via the website which includes managing and recording outgoing and incoming funds, thereby increasing efficiency and transparency in managing the organization's cash.